Identification and immunogenicity study of soluble protein derived from Pasteurella multocida serotype B / Noor Masyitah Jumahat - Jumahat, Noor Masyitah (2015)
Pasteurella multocida (P. multocida) serotype B is associated with hemorrhagic septicaemia (HS) disease endemic in Africa, India and Asian countries. It is causative agent of thriftily significant disease in livestock. Hence, this study purposed and aimed to identify and express an immunogenic soluble protein of P. multocida in efforts toward development of HS vaccine. Immunogenic - soluble protein was identified as lipoprotein B (plpB) using electrospray mass spectrometry. The size of expressed purified recombinant protein was approximately 39kDa. Immunogenicity study of the recombinant protein plpB was carried out using 6 groups of BALB/c mice. The groups were immunized with recombinant protein (Group 1), soluble recombinant protein (Group 2), insoluble recombinant protein (Group 3), vector (Group 4), soluble protein of P. multocida (Group 5) and PBS (Group 6) respectively. Mice in group 4 and 6 showed signs and symptom of HS after challenge with the parental strain (p-value < 0.05). However, immunised mice with purified recombinant protein did not show signs and symptoms of HS. Based on immunoblotting analysis, purified recombinant protein was significantly immunogenic (p-value < 0.05). Additionally, no inflammation was seen in the tissues of organs from mice immunized with purified recombinant protein, which indicates that recombinant protein was 100% protective towards P. multocida infection and eventually towards HS disease. Thus, this study shows that the recombinant protein lipoprotein B (plpB) is significantly immunogenic and could be a potential candidate in developing vaccine against HS.